El WIP como objetivo estratégico en la distribución de planta (2012)
This paper presents a model to generate the layout of a facility, minimizing the work in process (WIP) for a production system that uses multiple material handling systems. Using WIP as an objective in a facility layout problem is a novel approach. WIP is an operating performance measure that impacts directly in the production costs, and is generally not considered in facility layout problems. As a result, we present a model to design facility layouts with a better WIP performance than the ones designed by a model with a single material handling system